Mycorrhizal symbiosis benefited yield and fruit quality in Cabernet Sauvignon facing high temperatures combined with elevated CO2 in its first productive year - María Carmen Antolín; Daria Kozikova; Inmaculada Pascual; Idoia Garmendia; Nieves Goicoechea (Plant and Soil, 2026)
Aims Our objective was to assess whether mycorrhization could enhance the resilience of young Cabernet Sauvignon in its first year of production to elevated temperatures under current and future atmospheric CO 2 scenarios. Methods Two-year-old Cabernet Sauvignon grafted plants and divided into non-mycorrhizal and mycorrhizal, were subjected to four environments from fruit set to maturity: (1) ambient CO 2 and temperature; (2) ambient CO 2 and elevated temperature (ambient temperature + 4˚C); (3) elevated CO 2 (700 ppm CO 2 ) and ambient temperature; and (4) elevated CO 2 and temperature. Mycorrhizal fungi were co-inoculated with bacteria. Gas exchange, minerals and organic solutes in leaves were measured two weeks after fruit veraison. At maturity, yield and fruit quality were assessed. Results Mean maximum temperatures under ambient and elevated temperature were 32.4 and 36.6 °C, respectively. Photosynthesis increased under elevated compared to ambient CO 2 and temperature, especially in non-mycorrhizal plants. Cu, Zn and Fe decreased under elevated CO 2 and temperature in non-mycorrhizal plants. In mycorrhizal plants, Mn was higher under elevated CO 2 and temperature, and Cu and Fe were similar under elevated and ambient CO 2 and temperature. Yield, sugars and anthocyanins decreased in berries of non-mycorrhizal plants under elevated CO 2 and temperature, with an increase in antioxidant activity. Mycorrhization benefited yield and fruit quality under elevated temperature, especially when combined with elevated CO 2 . Conclusion Co-inoculation of mycorrhizal fungi and bacteria increased Cabernet Sauvignon thermoresistance by maintaining micronutrient levels under heat stress at levels similar to those at moderate temperatures, resulting in higher fruit yield and quality.

Response of Portulaca oleracea biomass and its rhizospheric microbiome to the application of solid and liquid slumgum from beekeeping industry transformed with Penicillium chrysogenum - Ángel Carrascosa-Robles; José Antonio Pascual; Jessica Cuartero; Inmaculada García-Romera; Gloria Andrea Silva-Castro; Ana de Santiago; Margarita Ros; Spyridon A. Petropoulos; María del Mar Alguacil (Plant and Soil, 2026)
Background and aims Slumgum, a by-product of the beeswax-rendering process, is a nutrient-rich organic waste with potential as a sustainable fertiliser. Unlike chemical fertilisers, which can degrade soil health and contribute to environmental pollution, slumgum may improve soil structure, enhance microbial activity, and support long-term soil fertility. This study assessed, for the first time, the effects of both solid and liquid slumgum, either transformed with Penicillium chrysogenum and non-transformed, on purslane ( Portulaca oleracea ) biomass and soil rhizosphere microbial communities. Methods The experiment involved applying different slumgum treatments to purslane plants, followed by the analysis of shoot biomass and foliar phosphorous content. Soil enzymatic activities related to carbon, nitrogen, and phosphorus cycles were measured. Additionally, bacterial and fungal community composition, diversity, and functional guilds in the rhizosphere were described. Results Both transformed solid and liquid slumgum along with untransformed liquid slumgum treatments increased purslane shoot biomass (by 60–77%) and foliar phosphorous content (by 87–100%) compared to the control. Slumgum treatments modified the microbial community composition, increasing saprotrophic fungi and reducing plant pathogens. Transformed solid slumgum also enhanced enzymatic activities involved in nutrient cycling, whereas the untransformed solid slumgum treatment promoted bacterial genes associated with denitrification. Conclusion Our findings highlight the potential of slumgum, particularly in its transformed forms, as a sustainable alternative to chemical fertilisers. Its application may improve soil fertility and crop productivity while reducing environmental impact. Further studies should investigate its long-term effects under field conditions and evaluate its economic feasibility.

A consortium of arbuscular mycorrhizal fungi and plant growth-promoting bacteria modulates wine grape ripening and composition under climate change conditions - Daria Kozikova; Johann Martínez-Lüscher; M. Carmen Antolín; Nieves Goicoechea; Inmaculada Pascual (Food Research International, 2026)

Effects of elevated temperature and shaded UV-B radiation exclusion on berry biochemical composition in four grape (Vitis vinifera L.) cultivars with distinct anthocyanin profiles - Haiqi Wang; Mingzhi Yang; Johann Martinez-Luscher; Ghislaine Hilbert-Masson; Eric Gomès; Inmaculada Pascual; Peige Fan; Junhua Kong; Zhenchang Liang; Zehua Xu; Yongjian Wang; Zhanwu Dai (Food Research International, 2025)

A balanced approach to the potential of octopus aquaculture - Ian G. Gleadall; Roger Villanueva; Gregory J. Barord; Zoe Doubleday; Felipe Aguado-Giménez; Nobuhiko Akiyama; Eduardo Almansa; Cheryl L. Ames; Alexander Arkhipkin; Otilio Avendaño; Chris Barrett; Giambattista Bello; et al. (Marine Policy, 2025)

ABA and defoliation improve phenolic composition of wine grapes while ABA reduces must free amino acid content and modifies its profile - Johann Martínez-Lüscher; Andrea Cabodevilla; Mohammad Abdullah; Andoni Iglesias; Ángel Zamarreño; José María García-Mina; Fermín Morales; Nieves Goicoechea; Inmaculada Pascual (Plant Science, 2025)

Fosfomycin in bacteraemic urinary tract infection due to multidrug-resistant Escherichia coli : insights of post hoc DOOR analysis of the FOREST trial - Jesús Sojo-Dorado; Inmaculada López-Hernández; Belén Gutiérrez-Gutiérrez; Sandra De la Rosa-Riestra; Fernando Docobo-Pérez; Alicia Hernánez-Torres; Álvaro Pascual; Jesús Rodriguez-Baño; Esperanza Merino de Lucas; Laura Escolà-Vergé; Elena Bereciartua; Elisa García-Vázquez; et al. (Infectious Diseases, 2025)

Grapevine varieties show different sensitivities to flavonoid alterations caused by high temperatures under two irrigation conditions - Inmaculada Pascual; Johann Martínez-Lüscher; Juan José Irigoyen; Nieves Goicoechea; M. Carmen Antolín (Food Research International, 2024)

New instrumentation in grapevine research: A dual respiration prototype for grape berries and whole bunch. The grape CO2/O2 respiratory quotient revisited - Fermín Morales; Andrea Cabodevilla; Inmaculada Pascual; Amadeo Urdiain (Computers and Electronics in Agriculture, 2024)

Global longitudinal strain assessment of cardiac function and extravascular lung water formation after diving using semi-closed circuit rebreather - María Martinez-Villar; Antonio Tello-Montoliu; Agustín Olea; Ángel Pujante; Daniel Saura; Silvia Martín; Nereo Venero; Ana Carneiro-Mosquera; Nuria Ruiz de Pascual; Noelia Valero; Miguel Martinez-Herrera; Inmaculada Ramírez-Macías; et al. (European Journal of Applied Physiology, 2022)

Connectivity of Natura 2000 potential natural riparian habitats under climate change in the Northwest Iberian Peninsula: implications for their conservation - Víctor Rincón; Javier Velázquez; Álvaro Pascual; Fernando Herráez; Inmaculada Gómez; Javier Gutiérrez; Beatriz Sánchez; Ana Hernando; Tomás Santamaría; Daniel Sánchez-Mata (Biodiversity and Conservation, 2022)

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Challenges for Sustained Observing and Forecasting Systems in the Mediterranean Sea - Joaquín Tintoré; Nadia Pinardi; Enrique Álvarez-Fanjul; Eva Aguiar; Diego Álvarez-Berastegui; Marco Bajo; Rosa Balbin; Roberto Bozzano; Bruno Buongiorno Nardelli; Vanessa Cardin; Benjamin Casas; Miguel Charcos-Llorens; et al. (Frontiers in Marine Science, 2019)

Is vegetative area, photosynthesis, or grape C uploading involved in the climate change-related grape sugar/anthocyanin decoupling in Tempranillo? - Carolina Salazar-Parra; Iker Aranjuelo; Inmaculada Pascual; Jone Aguirreolea; Manuel Sánchez-Díaz; Juan José Irigoyen; José Luis Araus; Fermín Morales (Photosynthesis Research, 2018)

From vineyards to controlled environments in grapevine research: investigating responses to climate change scenarios using fruit-bearing cuttings - Fermín Morales; María Carmen Antolín; Iker Aranjuelo; Nieves Goicoechea; Inmaculada Pascual (Theoretical and Experimental Plant Physiology, 2016)

Relationship of immunohistochemistry, copy number aberrations and epigenetic disorders with BRCAness pattern in hereditary and sporadic breast cancer - Rosa Murria Estal; Sarai Palanca Suela; Inmaculada de Juan Jiménez; Cristina Alenda Gonzalez; Cecilia Egoavil Rojas; Zaida García-Casado; Jose Antonio López Guerrero; María José Juan Fita; Ana Beatriz Sánchez Heras; Ángel Segura Huerta; Ana Santaballa Bertrán; Isabel Chirivella González; et al. (Familial Cancer, 2016)

Pharmacological Interventions to Ameliorate Neuropathological Symptoms in a Mouse Model of Lafora Disease - Arnaud Berthier; Miguel Payá; Ana M. García-Cabrero; Maria Inmaculada Ballester; Miguel Heredia; José M. Serratosa; Marina P. Sánchez; Pascual Sanz (Molecular Neurobiology, 2016)

BRCA1 and BRCA2 mutations in males with familial breast and ovarian cancer syndrome. Results of a Spanish multicenter study - Inmaculada de Juan; Sarai Palanca; Asunción Domenech; Lidia Feliubadaló; Ángel Segura; Ana Osorio; Isabel Chirivella; Miguel de la Hoya; Ana Beatriz Sánchez; Mar Infante; Isabel Tena; Orland Díez; et al. (Familial Cancer, 2015)

How will climate change influence grapevine cv. Tempranillo photosynthesis under different soil textures? - Urtzi Leibar; Ana Aizpurua; Olatz Unamunzaga; Inmaculada Pascual; Fermín Morales (Photosynthesis Research, 2015)

Novel and recurrent BRCA1/BRCA2 mutations in early onset and familial breast and ovarian cancer detected in the Program of Genetic Counseling in Cancer of Valencian Community (eastern Spain). Relationship of family phenotypes with mutation prevalence - Inmaculada de Juan Jiménez; Zaida García Casado; Sarai Palanca Suela; Eva Esteban Cardeñosa; José Antonio López Guerrero; Ángel Segura Huerta; Isabel Chirivella González; Ana Beatriz Sánchez Heras; Mª José Juan Fita; Isabel Tena García; Carmen Guillen Ponce; Eduardo Martínez de Dueñas; et al. (Familial Cancer, 2013)

The deletion of exons 3–5 of BRCA1 is the first founder rearrangement identified in breast and/or ovarian cancer Spanish families - Sarai Palanca; Inmaculada de Juan; Gema Perez-Simó; Eva Barragán; Isabel Chirivella; Eduardo Martínez; Óscar Fuster; Pascual Bolufer (Familial Cancer, 2013)

Low penetrance alleles as risk modifiers in familial and sporadic breast cancer - Eva Esteban Cardeñosa; Inmaculada de Juan Jiménez; Sarai Palanca Suela; Isabel Chirivella González; Ángel Segura Huerta; Ana Santaballa Beltran; María Casals El Busto; Eva Barragán González; Oscar Fuster Lluch; José Bermúdez Edo; Pascual Bolufer Gilabert (Familial Cancer, 2012)

Low prevalence of BRCA1 and BRCA2 mutations in the sporadic breast cancer of Spanish population - Inmaculada de Juan Jiménez; Eva Esteban Cardeñosa; Sarai Palanca Suela; Eva Barragán González; Ismael Aznar Carretero; Blanca Munárriz Gandía; Ana Santaballa Bertran; María Dolores Torregrosa Maicas; Carmen Guillén Ponce; Ana Beatriz Sánchez Heras; Ana Bayón Lara; Oscar Fuster Lluch; et al. (Familial Cancer, 2012)

Relationship of BRCA1 and BRCA2 mutations with cancer burden in the family and tumor incidence - Eva Esteban Cardeñosa; Pascual Bolufer Gilabert; Inmaculada de Juan Jiménez; Sarai Palanca Suela; Eva Barragán González; Virginia González Anguix; Enrique Lerma Alejos; Isabel Chirivella González; Ángel Segura Huerta; Carmen Guillén Ponce; Eduardo Martínez de Dueñas; Dolores Cuevas Cuerda; et al. (Familial Cancer, 2010)

Plant availability of heavy metals in a soil amended with a high dose of sewage sludge under drought conditions - Inmaculada Pascual; M. Carmen Antoln; Carlos Garca; Alfredo Polo; Manuel Snchez-Daz (Biology and Fertility of Soils, 2004)

Altered regulation of calcium channels and exocytosis in single human pheochromocytoma cells - Jesús M. Hernández-Guijo; Luis Gandía; Inmaculada Cuchillo-Ibáñez; Almudena Albillos; Jesús Novalbos; Fernando Gilsanz; Eduardo Larrañaga; Ricardo de Pascual; Francisco Abad; Antonio G. García (Pflügers Archiv - European Journal of Physiology, 2000)

Human adrenal chromaffin cell calcium channels: drastic current facilitation in cell clusters, but not in isolated cells - Luis Gandía; Inés Mayorgas; Pedro Michelena; Inmaculada Cuchillo; Ricardo de Pascual; Francisco Abad; Jesús M. Novalbos; Eduardo Larrañaga; A. G. García (Pflügers Archiv - European Journal of Physiology, 1998)